How does carrier status for recessive disorders influence reproductive decisions? A systematic review of the literature. (2nd December 2019) - Cannon, Jeffrey; Van Steijvoort, Eva; Borry, Pascal; Chokoshvili, Davit
ABSTRACT: Introduction : Carrier screening for recessive disorders is undertaken by prospective parents to inform their reproductive decisions. With the growing availability of affordable and comprehensive expanded carrier screening (ECS), it is expected that carrier screening will become a standard practice in the future. However, the impact of positive carrier screening results on the reproductive decisions of at-risk couples (ARCs) remains underexplored. Areas covered : We performed a systematic literature review to identify peer-reviewed publications describing the reproductive decisions of ARCs. Our search identified 19 relevant publications spanning the period 1994–2018. By synthesizing available evidence, we found that most ARCs chose to prevent the birth of an affected child and the decision to utilize preventive reproductive options was strongly influenced by the clinical nature of a disorder. However, there was also some heterogeneity in reproductive decisions within the same recessive disorders, suggesting that choices of ARCs can be influenced by factors other than the clinical nature of a disorder. Expert opinion : ECS is becoming increasingly common, which will result in the routine identification of many ARCs. Reproductive decision-making by ARCs is a complex and emotionally challenging process, highlighting the critical role of genetic counseling in the care for these potentially vulnerable patients.